Taxonomic revision of the genus Panca Evans, 1955 (Hesperiidae: Hesperiinae: Hesperiini: Moncina) with the description of two new species - de Medeiros, Adalberto Dantas; Dolibaina, Diego Rodrigo; Carneiro, Eduardo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2020)
The South American genus Panca Evans, 1955 and its respective species are revised. Previous to this study, the genus included solely its type species, Lerodea subpunctuli Hayward, 1934, until Panca moseri Dolibaina, Carneiro & O. Mielke, 2017 was described recently. However, as a result of a broader morphological study including closely related genera, we here propose that Panca assembles 12 species, most of which inhabit open environments such as the Cerrado biome and the natural grasslands of the Atlantic Forest biome. Eight species formerly included among other genera of Moncina are here combined with Panca: Panca satyr (Evans, 1955) comb. nov., Panca tobiasi (Mielke, 1992) comb. nov., Panca trogon (Evans, 1955) comb. nov., Panca steinhauseri (Dolibaina & A. Warren, 2015) comb. nov., Panca acroleuca (Plötz, 1884) comb. nov., and Panca mirnae (O. Mielke, Dolibaina, Carneiro & A. Warren, 2015) comb. nov. (all formerly in Artines Godman, 1901), Panca paulo (Bell, 1932) comb. nov. (formerly in Eutocus Godman, 1901), and Panca mictra (Evans, 1955) comb. nov. (formerly in Vidius Evans, 1955). Additionally, two new species are described from Brazil: Panca puri Medeiros, O. Mielke & Casagrande sp. nov. (from Pará, Pernambuco, Minas Gerais, Rio de Janeiro and Paraná) and Panca xavante Medeiros, O. Mielke & Dolibaina sp. nov. (from Mato Grosso, Goiás, Distrito Federal and Minas Gerais). A neotype for Apaustus acroleuca Plötz, 1884 is designated. Illustrations of the male and female genitalia and distribution maps are presented for all the species of Panca and an identification key is provided for both sexes.